2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591119
|View full text |Cite
|
Sign up to set email alerts
|

Development of a head impact monitoring “Intelligent Mouthguard”

Abstract: The authors present the development and laboratory system-level testing of an impact monitoring "Intelligent Mouthguard" intended to help with identification of potentially concussive head impacts and cumulative head impact dosage. The goal of Intelligent Mouthguard is to provide an indicator of potential concussion risk, and help caregiver identify athletes needing sideline concussion protocol testing. Intelligent Mouthguard may also help identify individuals who are at higher risk based on historical dosage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Also, the range of impact magnitudes, as well as impact locations confirmed that on-field data in this study fell within the ranges of calibration from the laboratory with the exception that the Virginia Tech Sensor 5 laboratory tests in the Appendix (Electronic supplementary material) did not calibrate the IMM response to facemask impacts. However, facemask impact calibrations have been published elsewhere, 6 Hedin et al, 31 Bartsch et al, 4 Bartsch et al, 3 Domel et al 15 submitted) and the impacts collected in this study fell within the published facemask calibration ranges.…”
Section: Discussionsupporting
confidence: 60%
“…Also, the range of impact magnitudes, as well as impact locations confirmed that on-field data in this study fell within the ranges of calibration from the laboratory with the exception that the Virginia Tech Sensor 5 laboratory tests in the Appendix (Electronic supplementary material) did not calibrate the IMM response to facemask impacts. However, facemask impact calibrations have been published elsewhere, 6 Hedin et al, 31 Bartsch et al, 4 Bartsch et al, 3 Domel et al 15 submitted) and the impacts collected in this study fell within the published facemask calibration ranges.…”
Section: Discussionsupporting
confidence: 60%
“…Upon enrollment into the study, 23 participants were instrumented with an IMM, which has been described and validated. 3,4,18 All mouthguards fit snugly on the participants' upper dentitions, and adjustments could be made if necessary for comfort of fit before use in sparring or competition. Participants wore the IMMs while research personnel captured time-stamped video recordings for all sparring sessions (n ¼ 54) and competitions (n ¼ 6).…”
Section: Methodsmentioning
confidence: 99%
“…3,4 When the Hybrid III head forms were used to assess IMM results within the impact acceleration profiles of American football and boxing, IMM data were correlated with reference data for PLA, PAA, and peak angular velocity ( R 2 ≥ 0.98 for each metric). 3,4,18 Improved coupling and error margins <5% represent a substantial improvement over other impact dosimeters. 3,4…”
mentioning
confidence: 96%
See 2 more Smart Citations